(3GdEQTGO Edi fLGI GdYHGOs - (3MSGe GdOjf CHh eMeO YHO Gddg Hf RjO GdYfSj GdeOMLjs ((3egOi Hf CMeO Hf eMeO Hf UdGM Hf YHOGdgd Hf eMeO Hf UdGM s)
(3ChdgG (B:s
(3Gddge Efi CYJQa dc HGdQHhHjI , hYf ShGc HGdYHhOjI aef gGgfG JYde Cf GdfLGI HWGYJg , hGdgdGc HeNGdaJg , hGdBf jbY GdEQTGO ddWGdH Edi WQjb GdfLGI djHdZ HPdc Edi gfF GdMjGI s
(3BNQgG (B:s
(3hef CMH ef ENhGfi JUMjM TF , eeG QhjJg Yf GdfHi egeG jXgQ ajg GdNdW hGdNWC gPG eY JMaXi ai eG QhjJ hENJHGQg ai JUMjM Pdc Je s
(3GfJgi GdeDda ef JCdjag SfI (B632(3g`s
(3HgG fXGe GdJYbjHIs
(3Ydi WQJgG Jedc eDQN SfI (B1242(3g` HGSe CMeO Hf UGdM GdMSfi GdegOis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs